Bismuth mediated barbier synthesis of α-homoallylic alcohols via a sigmatropic rearrangement in [bmim][HSO4]. Issue 5 (4th March 2021) - Chatterjee, Sucheta; Dey, Papiya; Kanojia, Seema V.; Chattopadhyay, Subrata; Goswami, Dibakar
Abstract: A novel protocol for the Bismuth metal mediated regioselctive crotylation of aldehydes yielding α -homoallylic alcohols has been developed using 20 mol% [bmim][HSO4 ] as a metal activator, as well as a mediator for regioconversion from the initially formed γ -regiomer. The present protocol minimizes the use of conventional solvents and proceeds with good yields and excellent regioselectivities. Graphical Abstract: